Rylene diimide-based alternate and random copolymers for flexible supercapacitor electrode materials with exceptional stability and high power density - Sharma, S.; Soni, R.; Kurungot, S.; Asha, S. K. (Journal of Physical Chemistry C, 2019)
Donor–acceptor pi-conjugated polymers are emerging as interesting electrode materials for supercapacitor device applications. They offer an exciting possibility of charge storage in both positive and negative electrodes because they are both p- and n-dopable. The ambipolar charging enables higher operating voltage, which can afford higher specific energy and power densities. The donor–acceptor design can be either donor-alternate-acceptor or donor-random-acceptor. This architectural variation has the potential to modify the charge storage; yet surprisingly not much literature data is available exploiting this aspect. This paper explores the alternate and random geometries of donor–acceptor π-conjugated polymers based on naphthalene diimide or perylene diimide (PDI) as the acceptor component and benzodithiophene (BDT) as the donor component and their application as composite electrode materials in a type III supercapacitor device. Results show that the donor–acceptor alternate design involving P(PDI-alt-BDT) is an excellent supercapacitor electrode material with specific capacitance of 113 F g–1 with excellent stability up to 4000 cycles and almost 100% retention of the initial capacitance in a single-electrode setup in a PC-LiClO4 organic electrolyte. A flexible supercapacitor device was also fabricated which shows areal capacitance of 35 mF cm–2 at a current density of 0.5 mA cm–2, which is promising for commercial applications.